1964
DOI: 10.1083/jcb.21.2.265
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscope Examination of Urinary Mucoprotein and Its Interaction With Influenza Virus

Abstract: A hemagglutination-inhibitory mucoprotein from h u m a n urine has been studied with the electron microscope. It consists of filaments, with diameters of 40 to > 2 4 0 A , composed of smaller fibrils. In the two-dimensional projection of the electron micrographs, the single fibrils often show a zig-zag course with a periodicity of 100 to 140 A; the single branch of a zigzag measures about 60 A in length and either 20 or 40 A in width. Still thinner fibrillar elements are observable with diameters of l0 A or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…In contrast, ␤-tectorin comprises only a single zona pellucida domain (12). The zona pellucida domain (31) is a feature shared by a number of different proteins, all of which are capable of forming filament-based matrices or gels (32)(33)(34)(35)(36)(37)(38). The presence of a common domain in both ␣-and ␤-tectorin has led to the suggestion that these two proteins may either selfassociate to form homomeric filaments or interact with each other to form heteromeric filaments via their zona pellucida domains and that these filaments correspond to the light and dark staining filaments that are visible in the collagenaseinsensitive, striated-sheet matrix of the tectorial membrane (12).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ␤-tectorin comprises only a single zona pellucida domain (12). The zona pellucida domain (31) is a feature shared by a number of different proteins, all of which are capable of forming filament-based matrices or gels (32)(33)(34)(35)(36)(37)(38). The presence of a common domain in both ␣-and ␤-tectorin has led to the suggestion that these two proteins may either selfassociate to form homomeric filaments or interact with each other to form heteromeric filaments via their zona pellucida domains and that these filaments correspond to the light and dark staining filaments that are visible in the collagenaseinsensitive, striated-sheet matrix of the tectorial membrane (12).…”
Section: Discussionmentioning
confidence: 99%
“…10 6 kDa. It is notable that these aggregates were directly visualized in several studies by electron microscopy [28,31,41,[46][47][48] and conditions and molecular mechanisms for their formation were established [46,47,[49][50][51][52] .…”
Section: Discovery Of Umod By Igor Tamm and Frank Lappin Horsfallmentioning
confidence: 99%
“…A number of chemical (elemental composition), biochemical (amino acid composition, carbohydrate content, supramolecular structure, molecular weight, pI and electrophoretic mobility), physicochemical (solubility, pH and thermal stability) and physical (viscosity, diffusion coefficient, ultraviolet and infrared absorption spectra, extinction coefficient, refractive index, and rheology) properties were determined in ongoing studies in the 1950s [25][26][27][28][29][30] and 1960s [31][32][33][34][35][36][37][38][39][40] , and re-evaluated in the 1970s [41][42][43][44][45] .…”
Section: Discovery Of Umod By Igor Tamm and Frank Lappin Horsfallmentioning
confidence: 99%
“…This is the only common feature shared by a number of different proteins (Fig. 7b) all of which either can or do form filament based matrices or gels (42)(43)(44)(45)(46)(47)(48), and it has been suggested that it may be the element that enables them to form filaments (3). The presence of this domain in both of the two major components of the filament based non-collagenous matrix of the mouse tectorial membrane suggests that these two proteins may either self-associate via their respective zona pellucida domains to form homomeric filaments, or interact with each other via their zona pellucida domains to form heteromeric filaments.…”
mentioning
confidence: 99%